2021
DOI: 10.1101/2021.01.21.427550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hearing loss is associated with delayed neural responses to continuous speech

Abstract: We investigated the impact of hearing loss on the neural processing of speech. Using a forward modelling approach, we compared the neural responses to continuous speech of 14 adults with sensorineural hearing loss with those of age-matched normal-hearing peers.Compared to their normal-hearing peers, hearing-impaired listeners had increased neural tracking and delayed neural responses to continuous speech in quiet. The latency also increased with the degree of hearing loss. As speech understanding decreased, ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 63 publications
6
14
0
Order By: Relevance
“…Previous literature showed that adults with hearing loss showed higher acoustic NT and later neural response latencies compared to normal hearing adults (Gillis et al, 2021a), which supports our hypothesis.…”
Section: Current Studysupporting
confidence: 91%
“…Previous literature showed that adults with hearing loss showed higher acoustic NT and later neural response latencies compared to normal hearing adults (Gillis et al, 2021a), which supports our hypothesis.…”
Section: Current Studysupporting
confidence: 91%
“…Increased latencies are often observed in more complex conditions with a higher task demand, like for example lower stimulus intensity, vocoded speech or speech in noise (Mirkovic et al, 2019; Verschueren et al, 2021; Kraus et al, 2020). The latency of the neural responses can also be related to neural processing efficiency (Bidelman et al, 2019; Gillis et al, 2021a). In more detail, a larger latency indicates that more processing time is required to process the same speech characteristics, showing reduced neural processing efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Decruy et al (2020b) and Fuglsang et al (2020) found increased envelope tracking for hearing-impaired listeners compared to age-matched normal-hearing listeners. The enhanced tracking in older listeners or listeners with a hearing impairment may be explained by a compensatory central gain mechanism (Parthasarathy et al, 2019; De Villers-Sidani et al, 2010; Chambers et al, 2016), recruitment of additional cortical resources (Brodbeck et al, 2018b; Gillis et al, 2021a) and increased listening effort and attention (Decruy et al, 2020a; Vanthornhout et al, 2019; Lesenfants and Francart, 2020). With an innovative artefact removal technique, Somers et al (2019) succeeded to analyse envelope tracking for cochlear implant listeners as well.…”
Section: Neural Tracking Of the Speech Envelopementioning
confidence: 99%